Current status of endoscopic submucosal dissection for early gastric cancer in Korea: role and benefits - Kim, Sang Gyun; Lyu, Da Hyun; Park, Chan Mi; Lee, Na Rae; Kim, Jiyoung; Cha, Youngju; Jung, Hwoon-Yong (The Korean journal of internal medicine, 2019)
This study was aimed to investigate the current clinical status of endoscopic submucosal dissection (ESD) for early gastric cancer (EGC) in Korea based on a National Health Insurance (NHI) database between 2011 and 2014. The claims data of ESD for EGC in Korean NHI were reviewed using material codes of Health Insurance Review and Assessment Service between November 2011 and December 2014. The current clinical status was analyzed in terms of treatment pattern, in-hospital length of stay (LOS), total medical costs, and en bloc resection rate according to the hospital type. A total of 23,828 cases of ESD for EGC were evaluated. ESD was performed in 67.4% of cases in tertiary care hospitals, 31.8% in general hospitals, and 0.8% in hospitals, respectively. The median LOS was 5 days, and total median medical costs was approximately 1,300 US dollars. En bloc resection rate was 99%; 8.5% of cases underwent additional treatment within 90 days ESD, and 5.5% in 91 to 365 days after ESD. The clinical status was not significantly different according to the year and hospital type. A majority of ESD for EGC were performed in tertiary care hospitals in Korea. The clinical status showed excellent clinical outcomes and did not differ by the year and between the types of hospitals in Korea.